MCQs in Medical virology - Steven H Myint (Chapman and Hall, 1995)
The book is a study guide and not a set of examination questions with answers. The first half of the book contains questions that are numbered identically to answers set out in the second section. The frist few questions or answers are on general aspects of viral infections pertinent to that system, then specific viruses are discussed. There is, usually one question on the virus otslf and then questions that cover the clinical manifestations, diagnosis and management of infections caused by that virus. The questions on the biology of the viruses are set in a different typescript